Introducing augmented reality in early childhood literacy learning - Zilong Pan; Mary Frances López; Chenglu Li; Min Liu (Association for Learning Technology, 2021)
Augmented reality (AR) as an emerging technology has gradually been incorporated into educational contexts; however, the cases that incorporate AR into early childhood contexts are underrepresented and especially scant in the literacy domain. Aiming to measure the impact of AR on early childhood learning and motivation in the literacy domain, this study brought an application into six pre-kindergarten classrooms by introducing three experimental classrooms to an AR centre while others engaged with a two-dimensional (2D) version of the same material. Bayesian analysis revealed that rapid letter naming rates grew for all children involved in the study. It increased by 6.28% among children in the experimental AR group and 3.35% in the control 2D group. Growth in rates of motivation was similar among experimental (11.5%) and control (10.9%) groups. These findings suggest that three-dimensional images of letters might help with rapid letter naming skills, and animations available in both versions may be the reason of increases in motivation. Teacher interviews presented positive views towards AR, and instructional implications were provided by teachers for incorporating the technology into early childhood classrooms.